Inovasi Pengolahan Ikan dalam Perspektif Ekonomi Biru - Minarti Minarti; Eliyanti Agus Mokodompit (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The purpose of this study is to analyze fish processing innovations in the context of blue economy in various regions of Indonesia. The method used in this study is an article review research method with a qualitative descriptive approach using 5 relevant scientific article sources from accredited journals. The research analysis method uses qualitative descriptive analysis. The results show that fish processing innovations through modern technologies such as freeze drying, controlled fermentation, and bioactive-based processing have provided significant economic added value. Various regions in Indonesia have developed innovative products such as high-protein fish flour, export-quality surimi, and functional fermented fish products that support blue economy principles through sustainable utilization of marine resources.